The influence Bladder Training Initiation to the Urine Residual of Stroke Patients with Urine Catheter - Hidayati, Wahyu (Nurse Media Journal of Nursing, 2011)
Background: The stroke patients usually experience with various dysfunction, including disturbance in elimination because of neurogenic bladder. Urine residue can be used to detect the bladder function in contracting and voiding urine.Purpose:This research aimed to compare bladder training initiation after stroke patients after the patients passedthe acute phase and one day before the urine catheter was removed.Methods:This research was quasy experimental studyposttest-only design with a comparison group design. The sample in this research was takenby purposive random sampling method. The residual urinewas measuredwithbladder scanand was recorded in the observation sheet.Results:The mean volume of the residual urineinthe treatment group was less(M= 54,00 ml; SD=144,22 ml) if compared with the residualurine volume in the control group (M= 101,71 ml; SD=42,55 ml). The mean differences ofbladder training both in the treatment and the control groups which was analyzed with t-test independent, there wes no differences between residualurine volume in bothgroups (p=0,84).Conclusion: Therefore,the health institution shouldconsider developingthe system and made a procedure in bladder training program.The nurse also should preverbladder training before the urine catheter was removal.Keywords: Bladder training, stroke patient, residual urine